(untitled) (Annals of Medical Research, 2021)
Aim: Non-operating room anesthesia is frequently used in all areas. Gastrointestinal endoscopy is one of the procedures requiring sedation outside the operating room. This study aimed to investigate the drugs used for sedation and the complications during gastrointestinal procedures in our hospital. Materials and Methods: The files of the patients who underwent anesthesia for gastrointestinal endoscopy between 01.01.2018- 31.12.2018 in our hospital were retrospectively reviewed. ASA score, age, gender, vital signs, drugs, doses, complications, and need for intensive care were evaluated. Results: A total of 508 patients were sedated. The 187 cases (36.3%) were male, and 321 (63.2%) were female. The mean age was 54.9 ± 15.6 years. Two hundred fifty-two cases (49.6%) were found to be ASA II. Colonoscopy was performed in 134 cases (26.4%), gastroscopy in 270 cases (53.1%), both colonoscopy and gastroscopy in 99 cases (19.5%), and PEG in 5 cases (1%). The most frequently used anesthetic drug in sedated patients was observed to be propofol. Complications occurred in 28 patients (5.5%). Conclusions: Drug selection becomes crucial in non-operating room anesthesia applications in terms of early recovery and patient safety. In this study, it was seen that the most used drug was propofol, and accordingly, it was concluded that mortal complications were not observed.